2020
DOI: 10.1016/j.sjbs.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Induced alteration of rat erythrocyte membrane with effect of pyrethroid based compounds

Abstract: The effects of tetramethrin and prallethrin exposure on plasma total proteins, free amino acids, albumins, urea, urea nitrogen, uric acid, creatinine were tested. Serum SGOT, SGPT and lipid profile, antioxidants super oxide dismutase (SOD), catalase, GSH, G-Px, phospholipids, cholesterol, C/P ratio in membranes of erythrocyte and membrane fluidity were analyzed. The reason of the study were analyzed to examine the possessions of mosquito repellent pyrethroid (MRP) based compounds tetramethrin and prallethrin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…A significant increase (about 3.5 folds) in the content of GSH in rats erythrocytes after CYP treatment showed pro-oxidant conditions in the RBCs, which may be an initial adaptive response to increased oxidative stress in CYP-treated erythrocytes (Kale et al, 1999). Our results in the same way with Liu et al (2020) who found that treating rats with pyrethroid insecticides tetramethrin and prallethrin induced elevation of GSH in erythrocytes.…”
Section: Discussionsupporting
confidence: 88%
“…A significant increase (about 3.5 folds) in the content of GSH in rats erythrocytes after CYP treatment showed pro-oxidant conditions in the RBCs, which may be an initial adaptive response to increased oxidative stress in CYP-treated erythrocytes (Kale et al, 1999). Our results in the same way with Liu et al (2020) who found that treating rats with pyrethroid insecticides tetramethrin and prallethrin induced elevation of GSH in erythrocytes.…”
Section: Discussionsupporting
confidence: 88%
“…[36] Alterations in plasma profile and lipid homeostasis were evident in rats exposed to tetramethrin and prallethrin via the nasal route. [37] Retention of native and oxidized LDL in the aorta, altered levels of cholesterol and HDL due to permethrin or bifenthrin induced toxicity in rats, [38,39] disturbances in the plasma biomarkers (inflammatory cytokines and that of liver function) by deltamethrin, [40] increased levels of plasma cholesterol and triglycerides in rats exposed to cypermethrin [41] and DNA damage in the peripheral lymphocytes of farmers who sprayed pesticides (deltamethrin) [42] are some recent reports related to the effects of pyrethroids on the hematological parameters. In this study, we observed disturbances in the levels of serum biomarkers that define liver function and lipid reported in apparently healthy subjects in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified a novel bacterial isolate G. cholesterolivorans A16 with strong tetramethrin degradation activity. Strain A16 utilized tetramethrin as the sole car-bon source for its growth over a wide range of temperatures (20-40 • C) and pH values (5)(6)(7)(8)(9), indicating that the strain has excellent applicability in different environments. It is noteworthy that strain A16 tolerated and degraded tetramethrin up to a concentration of 800 mg•L −1 , thus giving it an exceptional ability to colonize ecological niches where pesticide concentrations are high.…”
Section: Discussionmentioning
confidence: 99%
“…Strain A16 was capable of rapidly degrading tetramethrin without a lag phase over a wide range of temperatures (20-40 • C) and pH values (5)(6)(7)(8)(9). This is an important feature of bioremediation by organisms in a variable environment [41].…”
Section: Optimization Of Tetramethrin Degradation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation